2008
DOI: 10.1021/jp8040567
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study of Noncovalent Hybridization of Carbon Nanotubes by Single-Stranded DNA in Water

Abstract: Recent discovery that single-stranded DNA (ssDNA) binds to carbon nanotubes with high affinity to form soluble hybrids has received great attention as a promising approach to solving the long-standing problem of nanotube solubilization and separation. The mechanism of this process, including the nature of the DNA-nanotube interactions and the molecular structure of the hybrids is still not well understood. Here, we use all-atom replica-exchange molecular dynamics simulations to study the association of several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 84 publications
6
79
2
Order By: Relevance
“…atomic force microscopy (AFM) studies cannot be used to determine whether wrapping occurs because the probes do not have sufficient resolution to distinguish wrapping from some other type of arrangement such as adsorption as a linear chain rather than a helix. Computer simulations 16,17 have been of great utility in predicting the nature of polymer-nanotube adsorption; however under certain conditions both random 18,19 and inserted polymer 20,21 have been found to be the lowest energy adsorptive state. In this author's opinion, the number of experimental studies that have confirmed such predictions is not large enough to fully trust such computer simulations.…”
Section: Reviewmentioning
confidence: 99%
“…atomic force microscopy (AFM) studies cannot be used to determine whether wrapping occurs because the probes do not have sufficient resolution to distinguish wrapping from some other type of arrangement such as adsorption as a linear chain rather than a helix. Computer simulations 16,17 have been of great utility in predicting the nature of polymer-nanotube adsorption; however under certain conditions both random 18,19 and inserted polymer 20,21 have been found to be the lowest energy adsorptive state. In this author's opinion, the number of experimental studies that have confirmed such predictions is not large enough to fully trust such computer simulations.…”
Section: Reviewmentioning
confidence: 99%
“…Although carbon nanotubes were observed in the bridge of cytokinesis and induced multi-polar mitotic spindles, the centrosomes were not amplified, but fragmented during cell division. In contrast to asbestos, the SWCNT have a strong association with the centrosome as well as the DNA (Li et al 2006a(Li et al , 2006bMartin et al 2008;Sargent et al 2009b). Although chrysotile fibers have low tensile strength and are brittle (Langer and Nolan 1994), carbon nanotubes can sustain a great deal of force before breaking (Pampaloni and Florin 2008).…”
Section: Comparison Of Carbon Nanotubes To Asbestosmentioning
confidence: 99%
“…Thus, quantum mechanics, molecular modelling and molecular simulation techniques provide representations of nanosystems at the atomic level with electronic resolution, offering a suitable framework for the characterization of diverse physical-chemical properties of nanosystems. Advancing in these efforts, the reports of several molecular dynamics (MD) simulations of nanoparticles and other nanosystems demonstrated the suitability of these computer-based techniques to explore and understand basic properties of nanoparticles and nanomaterials (Cieplak and Thompson, 2008;Khurana et al, 2006;Martin et al, 2008;Zimmerli and Koumoutsakos, 2008). Moreover, these tools provide a unique source of information not only to model basic nanoparticle properties, but also to gain insight into interactions with biological systems.…”
Section: New Challenges For Bioinformatics and Computational Chemistrmentioning
confidence: 99%